The impact of unemployment insurance on job creation - Silva, Maria Inês Baptista Ramos da (2022)
Unemployment insurances are perceived as major benefits to support workers in their job findings. This thesis contributes to the pre-existent literature through researching the impact of the unemployment benefits on the companies’ hirings and permanent layoffs, due to a lack of research on this matter. Using state and firm-specific variables, this study analyses the absolute and percentage impact on number of companies’ employees. For two of the overall performed regression models, higher amounts of unemployment insurances seem to impact positively the number of companies’ employees.